The folk song "The bridge of Arta". Bridging modern Greek literature and drama in an educational context - Papadopoulos, Simos; Basoukou, Lina (Epistēmēs Metron Logos, 2023)
This paper presents the creative use of dramatic tension techniques in teaching literature at secondary school level, with a specific focus on the folk song "The Bridge of Arta." The paper describes the main principles of the Curriculum for the teaching of Literature in Secondary Education in terms of expanding the teaching of texts within the field of dramatic art. It outlines the objectives of the proposal for employing dramatic techniques in this poem and analyzes the plot of the poem. The paper then suggests applications of experiential practice to enhance the elements of dramatic tension within the literary text. Additionally, it discusses the benefits of theatrical exploration in enriching the students' points of view.